2022
DOI: 10.1097/gme.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

Dynapenic-abdominal obesity as an independent risk factor for chronic kidney disease in postmenopausal women: a population-based cohort study

Abstract: Dynapenic-abdominal obesity, as determined by low handgrip strength and high waist circumference values, was associated with increased risk of chronic kidney disease in postmenopausal women. The dynapenic-abdominal obese group displayed lower levels of an estimated glomerular filtration rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, this previous study excluded subjects with severe CKD symptoms, and the number of subjects was small, including only 123 patients with CKD. In another previous study, the incidence of CKD was 1.82 times higher in postmenopausal women than in healthy participants [40]. However, this previous study was disadvantaged in that there is a criterion for subjects who are postmenopausal women.…”
Section: Discussionmentioning
confidence: 83%
“…However, this previous study excluded subjects with severe CKD symptoms, and the number of subjects was small, including only 123 patients with CKD. In another previous study, the incidence of CKD was 1.82 times higher in postmenopausal women than in healthy participants [40]. However, this previous study was disadvantaged in that there is a criterion for subjects who are postmenopausal women.…”
Section: Discussionmentioning
confidence: 83%
“…8 Furthermore, hormonal changes during menopause can lead to obesity. Choi et al 9 reported that abdominal obesity in postmenopausal women was an independent risk factor for the development of CKD.…”
mentioning
confidence: 99%